BIOACCUMULATION DYNAMICS OF HEAVY METALS IN Oreochromis nilotycus: PREDICTED THROUGH A BIOACCUMULATION MODEL CONSTRUCTED BASED ON BIOTIC LIGAND MODEL (BLM) - Sri Noegrohati (Indonesian Journal of Chemistry, 2006)
In estuarine ecosystem, sediments are not only functioning as heavy metal scavenger, but also as one of potential sources for heavy metals to the ecosystem. Due the capability of aquatic organisms to accumulate heavy metals, there is possibility of heavy metals to exert their toxic effect towards the organisms and other organisms positioned in higher trophic level, such as fish, and further to human beings. To understand the different processes of heavy metal bioaccumulation in a dynamic manner, a bioaccumulation model is required. Since bioaccumulation starts with the uptake of chemical across a biological membrane, the bioaccumulation model was constructed based on Biotic Ligand Model (BLM). The input for the model was determined from laboratory scale simulated estuarine ecosystem of  sediment-brackish water (seawater:Aquaâ 1:1) for determining the heavy metal fractions in sediments; simulated Oreochromis nilotycus - brackish water (fish-water) ecosystem for determining the rate constants; simulated fish-water-sediment ecosystem for evaluating the closeness between model-predicted and measured concentration, routes and distribution within specific internal organs. From these bioaccumulation studies, it was confirmed that the internalization of metals into the cells of gills and internal epithelias follows similar mechanisms, and governed mostly by the waterborne or hydrophilic heavy metals. The level of hydrophilic heavy metals are determined by desorption equilibrium coefficients, 1/KD, and influenced by salinity. Physiologically, the essential Cu and Zn body burden in O. nilotycus are tightly homeostasis regulated, shown as decreasing uptake efficiency factor, EW, at higher exposure concentrations, while non essential Cd and Hg were less or not regulated. From the distribution within specific internal organs, it was revealed that carcass was more relevant in describing the bioaccumulation condition than liver. It is clear that every heavy metal has its own bioaccumulation dynamics, depend to the metal studied and environmental conditions, however the obtained parameters are applicable to bioaccumulation of Cd and Hg in natural estuarine ecosystem of Segara Anakan, Central Java.